A checklist and key for the identification of bess beetles (Coleoptera: Passalidae) of Argentina - Jiménez-Ferbans, Larry; Reyes-Castillo, Pedro; Schuster, Jack C.; Salazar-Niño, Karen (Zootaxa, 2013)
Based on field collections, museum specimens and literature review, we present a checklist of Argentine Passalidae, with a key to their identification. A total of five genera and 24 species are listed, including Passalus quadricollis, Passalus perplexus and Passalus elfriedae as first records for the country.